Review of Naming What We Know. Threshold Concepts of Writing Studies (Classroom Edition). Edited by Linda Adler-Kassner and Elizabeth Wardle (2016). Logan: Utah State University Press. - Kerrigan, Paráic; Farrell, Alison (Journal of Academic Writing, 2018)
This is a review of the book Naming What We Know. Threshold Concepts of Writing Students (Classroom Edition) by Linda Adler-Kassner and Elizabeth Wardle (Utah State University Press, 2016).